Identification of Rainfall Intensity by Using Bahir Dar C-band Weather Radar products - Abebe Kebede Habtegebreal; Abebaw Bizuneh Alemu ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2019)
Observation of rainfall accumulation, distribution and wind direction spatially and temporally is very essential for meteorologists and hydrologists in the Upper Blue Nile basin and different locations of Ethiopia. The Bahir Dar (BAH) Cband weather radar used to estimate the intensity, amount and distribution of precipitation with a high resolution temporally and spatially. It is dual polarization with horizontal and vertical reflectivity; six variables are used to determine the hydrometer and non-hydrometer types, shape and sizes of targets up to range of 250 km and 450 km at constant altitude plan position indicator (CAPPI) and plan position indicator (PPI) products. From our first observation, we used different types of products to observe rainfall intensity, distribution, wind direction and warnings across Upper Blue Nile. For RainN on 01 July 2016 the rainfall distribution over twenty four hours (24 Hr) UTC at Bahir Dar, parts of lake Tana, most northern parts, western parts of Gondar town, and south western parts of lake Tana a resolution of 809 m/Pixel with frequency of 600 Hz the maximum rainfall accumulation 91.6 mm was achieved. By using CAPPI product with vertical height of 1 km on 26 June 2016 the maximum reflectivity 53.5 dBZ is observed.